DAYA TERIMA BISKUIT “JATISAR” BAGI BALITA STUNTING - Maria F Vinsensia D P Kewa Niron; Maria Goreti Pantaleon; Jane Austen Peni; Regina Maria Boro; Agustina Setia; Anak Agung Ayu Mirah Adi (Journal of Innovation Research and Knowledge, 2025)
Biscuits are a type of food made from wheat flour combined with other ingredients through a heating and molding process. This widely recognized food is often used as a medium for fortification, allowing additional nutrients to be consumed by more people. One of the high-protein food ingredients is sardines. Besides sardines, titi corn can also be used as a protein source because it contains a relatively high amount of protein. This study aimed to determine the acceptability and nutritional content of biscuits substituted with titi corn flour and sardine flour. The study employed a Completely Randomized Design (CRD) consisting of original (control) biscuits and formulated biscuits. The results indicated that the selected formulated biscuit was formula A1 (45% titi corn flour and 5% sardine flour). The best formula of titi corn flour and sardine flour biscuits can be consumed as a snack, especially by toddlers, with a serving size of three 15-gram pieces per snack time to help meet their nutritional needs, making it an effective additional nutrient source in combating stunting